Braucht Ostdeutschland eine neue Technologiepolitik? - Implikationen aus der Funktionsfähigkeit des Marktes für FuE nach der Transformation - Ralf Müller (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2001)
– Technology policy is a major part of government's efforts in contributing to East Ger-many's economic recovery. However, even a decade after unification East Germany does not produce sufficient technology goods. Thus, the question is whether technology policy is either not suitable or inefficient in tackling East Germany's deficits. A special technology policy for East Germany is justified by the lack of regional networks for technology firms; without a compensating policy East Germany would continue to lag behind West Germany also with respect to incomes. Yet only a few of the policy in-struments applied so far are efficiently dealing with these deficits. Thus, a future technology policy for East Germany should - mainly by the supply of R&D-infrastructure - support implementation of these kinds of networks.
urn:nbn:de:gbv:3:2-19987
Keywords: O31; O32; O38; 330; Forschungs- und Technologiepolitik; Wirkungsanalyse; Industrielle Forschung; Unternehmensnetzwerk; Neue Bundesländer